FEASIBILITY OF EDUCATIONAL MEDIA FOR STIMULATION OF TODDLER DEVELOPMENT WITH SNAKE AND LADDER GAMES - Wanodya Hapsari; Diki Retno Yuliani; Fitria Zuhriyatun (Universitas Karya Husada Semarang, 2024)
This research was carried out to stimulate the development of toddlers with educational media for snake and ladder games. This is necessary because if a child does not develop properly, it will experience delays in emotional, social, spiritual, intellectual and moral development. Research that has been carried out previously using various media. Unfortunately, the media is mostly carried out individually and even though some are in groups, it is only one direction. Therefore, this study seeks to stimulate the development of toddlers with educational media of snake and ladder games in an effort to increase knowledge about stimulation of toddler development because it has advantages, applied in groups so that it is more interactive. The goal is to determine the feasibility of stimulating the development of toddlers with educational media for snake and ladder games. The method used is Research and Development, which refers to the Instructional Design research and development model with the ADDIE approach. Validation of material experts is carried out by pediatricians, lecturers and midwives of the Health Center. Product implementation to users, namely parents of toddlers. Conclusion for educational media to stimulate toddler development with snake and ladder games is declared feasible to use, an alternative educational media with a percentage of 92%.